A Hundred Years of Bacteriophages: Can Phages Replace Antibiotics in Agriculture and Aquaculture? - Carmen Sieiro; Lara Areal-Hermida; Ángeles Pichardo-Gallardo; Raquel Almuiña-González; Trinidad de Miguel; Sandra Sánchez; Ángeles Sánchez-Pérez; Tomás G. Villa (MDPI AG, 2020)
Agriculture, together with aquaculture, supplies most of the foodstuffs required by the world human population to survive. Hence, bacterial diseases affecting either agricultural crops, fish, or shellfish not only cause large economic losses to producers but can even create food shortages, resulting in malnutrition, or even famine, in vulnerable populations. Years of antibiotic use in the prevention and the treatment of these infections have greatly contributed to the emergence and the proliferation of multidrug-resistant bacteria. This review addresses the urgent need for alternative strategies for the use of antibiotics, focusing on the use of bacteriophages (phages) as biocontrol agents. Phages are viruses that specifically infect bacteria; they are highly host-specific and represent an environmentally-friendly alternative to antibiotics to control and kill pathogenic bacteria. The information evaluated here highlights the effectiveness of phages in the control of numerous major pathogens that affect both agriculture and aquaculture, with special emphasis on scientific and technological aspects still requiring further development to establish phagotherapy as a real universal alternative to antibiotic treatment.